2002
DOI: 10.1046/j.1365-2443.2002.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

A minigene containing four discrete cis elements recapitulates GATA‐1 gene expression in vivo

Abstract: Background:  The GATA‐1haematopoietic enhancer (G1HE), located between 3.9 and 2.6 kb 5′ to the haematopoietic first exon, is essential for GATA‐1 gene transcription in erythroid cells. However, G1HE is not sufficient to confer tissue specificity on the GATA‐1 gene in vivo, indicating that additional regulatory sequences are necessary. Results: We demonstrate here that two other upstream promoter elements containing a double GATA motif or two CACCC boxes are also indispensable for reporter gene expression in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 22 publications
2
57
0
Order By: Relevance
“…The G1HRD can recapitulate Gata1 gene expression sufficiently enough to sustain embryonic and adult hematopoiesis (29,30). This can also be achieved by a 1-kb artificial mini-gene composed of the IE exon and four discrete cis-regulatory elements within the G1HRD (31). Substantiating these findings, our study showed that hemizygous males with congenital deletion of the IE exon die in utero.…”
Section: Discussionsupporting
confidence: 64%
“…The G1HRD can recapitulate Gata1 gene expression sufficiently enough to sustain embryonic and adult hematopoiesis (29,30). This can also be achieved by a 1-kb artificial mini-gene composed of the IE exon and four discrete cis-regulatory elements within the G1HRD (31). Substantiating these findings, our study showed that hemizygous males with congenital deletion of the IE exon die in utero.…”
Section: Discussionsupporting
confidence: 64%
“…A number of studies have addressed the regulatory mechanisms by which Gata1 gene expression is regulated through the use of a G1HRD-based b-galactosidase reporter transgenic mouse system. These analyses have revealed the existence of multiple cis-regulatory elements that confer lineage-and stage-specific Gata1 gene expression [14,20,26,27].…”
Section: Sequences and Mechanisms That Regulate Gata1 Transcriptionmentioning
confidence: 99%
“…Of interest, GATA-1 is also expressed as distinct mRNA isoforms in blood cells and testis under the control of two alternative promoters (Ito et al, 1993). While GATA-1 expression in hematopoietic tissues is under the control of the combination of the GATA-1 site and three other distinct regulatory elements (Tsai et al, 1991;Ohneda et al, 2002), the regulatory mechanisms for GATA-1 expression in testis remains to be defined. The possibility that a distinct regulatory network regulates HEMGN expression in testis is suggested by the observation that the 5Ј upstream sequence of the HEMGN-t exon 1t contains binding sites for the Sox-5 transcription factor, which is highly expressed in round spermatids (Denny et al, 1992).…”
Section: Discussionmentioning
confidence: 99%